Global research mapping of substance use disorder and treatment 1971–2017: implications for priority setting - Bach Xuan Tran (Substance Abuse Treatment, Prevention, and Policy, 2019)
Abstract Background Globally, substance use disorders are prevalent and remain an intractable public health problem for health care systems. This study aims to provide a global picture of substance use disorders research. Methods The Web of Science platform was used to perform a cross-sectional analysis of scientific articles on substance use disorders and treatment. Characteristics of publication volume, impact, growth, authors, institutions, countries, and journals were examined using descriptive analysis and network visualization graphs. Results Thirteen thousand six hundred eighty-five papers related to illicit drugs (5403), tobacco (4469), and alcohol (2137) use disorders and treatment were published between 1971 and 2017. The number of publications on Mindfulness and Digital medicine topics had the highest increase with more than 300% since 2003–2007 despite later presence than other methods. The number of papers on other non-pharmaceutical therapies (behavioral therapy, cognitive behavioral therapy, skills training or motivational interviewing) grew gradually, however, the growth rate was lower every 5-year period. The United States is the substance use disorder research hub of the world with the highest volume of publications (8232 or 60.2%) and total citations (252,935 or 65.2%), number of prolific authors (25 of top 30 or 83%) and institutions (24 of top 26 or 92%), formed the most international research partnerships (with 96 distinct countries). The international collaboration followed a pattern based on geographic proximity and cultural similarity. Conclusions This study offers a comprehensive picture of the global trend of publications of substance use disorder. Findings suggest a need for research policy that supports the examination of interventions that culturally adhere to different local contexts to address substance use disorder in communities.